Multidimensional monitoring of recovery status and implications for performance - Heidari, J.; Beckmann, J.; Bertollo, M.; Brink, M.; Kallus, K. W.; Robazza, C.; Kellmann, M. (International Journal of Sports Physiology and Performance, 2019)
Monitoring recovery in the context of athletic performance has gained significant importance during recent years. As a systematic process of data collection and evaluation, the monitoring of recovery can be implemented for various purposes. It may help prevent negative outcomes of training or competition, such as underrecovery, overtraining, or injuries. Furthermore, it aims to establish routines and strategies necessary to guarantee athletes` readiness for performance by restoring their depleted resources. Comprehensive monitoring of recovery ideally encompasses a multidimensional approach, thereby considering biological, psychological, and social monitoring methods. From a biological perspective, physiological (eg, cardiac parameters), biochemical (eg, creatine kinase), hormonal (eg, salivary cortisol), and immunological (eg, immunoglobulin A) markers can be taken into account to operationalize training loads and recovery needs. Psychological approaches suggest the application of validated and reliable psychometric questionnaires (eg, Recovery-Stress Questionnaire for Athletes) to measure a subjective perception of recovery, as well as the subjective degree of training- or competition-induced fatigue. Social aspects also play a role in performance monitoring and may hence provide essential performance-related information. The implementation of a monitoring routine in athletic environments represents a continuous process that functions as an effective addition to training and depends on a range of conditions (eg, organizational regulations, commitment of athletes). Current research in the field of monitoring aims to establish individualized monitoring regimens that refer to intraindividual reference values with the help of innovative technological devices.